Evaluasi Pembelajaran Experiential Learning terhadap Pembentukan Kecerdasan Spiritual Siswa pada Pendidikan Agama Islam - Komaruddin; Hakim, M. Ikhwanul; Manap, Abdul (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
This study aims to evaluate the effectiveness of the Experiential Learning model in developing students’ spiritual intelligence in Islamic Religious Education (PAI) at MTs NW Teko. The Experiential Learning approach is considered capable of bridging the gap between theoretical religious knowledge and the practical application of spiritual values in daily life. This research employed a mixed-methods design, combining a quantitative quasi-experimental approach with a qualitative case study. The subjects were eighth-grade students of MTs NW Teko. Data were collected through questionnaires, observations, interviews, and documentation. Quantitative analysis was used to measure the effectiveness of the learning model on students’ spiritual intelligence, while qualitative analysis identified supporting and inhibiting factors in its implementation. The findings reveal that the Experiential Learning model has a significant impact on enhancing students’ spiritual intelligence. Students demonstrated higher religious awareness, social responsibility, and reflective understanding of their spiritual experiences. Qualitative results indicate that the key supporting factors include strong teacher and school support, active student engagement, and a religiously conducive school environment. Meanwhile, the main inhibiting factors are limited facilities and time, varying levels of students’ spiritual maturity, and methodological challenges in assessing affective aspects. Overall, the study concludes that the success of spiritual intelligence development through Experiential Learning depends greatly on the collaboration among teachers, students, and the school environment.